Comparison of Rockall Score and MELD Score for Predicting in Hospital Mortality Patients with Vericeal Bleeding (Journal of Fatima Jinnah Medical University, 2024)
Background: It has been shown in several studies that Rockall score and MELD score are significantly high in patients who died due to variceal bleeding, hence these scores can be reliably used to predict in-hospital mortality and preventive measures can be taken in earlier phase to prevent mortality. The Objective of this study is determine the in-hospital mortality in patients with variceal bleeding due to cirrhosis and to compare the mean Rockall score and MELD score in patients with or without in-hospital mortality after variceal bleeding.Patients and Methods: The Observational study was conduct at Department of Gastroenterology, DQH Hospital, Gujranwala from June to December 2019. The Cirrhotic patients having age 16-70 years of either gender presenting with variceal bleeding that was diagnosed when there was blood in vomiting due to variceal hemorrhage detected on EGD were enrolled. Demographic details like name, age, gender, BMI, duration of variceal bleeding was obtained. At presentation, Rockall score and MELD score was calculated. The data was analyzed on SPSS version 21.0. Mean Rockall score and MELD score was compared in patients with or without in-hospital mortality by using independent samples t-test. P-value
Keywords: In-hospital; Mortality; Variceal, Bleeding; Cirrhosis; Rockall score; MELD score